Koi Herpesvirus Disease (KHVD) - Kathleen H. Hartman; Roy P. Yanong; Deborah B. Pouder; Barbara Denise Petty; Ruth Francis-Floyd; Allen C. Riggs; Thomas B. Waltzek (EDIS, 2013)
Koi herpesvirus (KHV) is a highly contagious virus that causes significant morbidity and mortality in common carp varieties. Common carp is raised as a foodfish in many countries and has also been selectively bred for the ornamental fish industry where it is known as koi. The first recognized case of KHV occurred in the United Kingdom in 1996. Since then other cases have been confirmed in almost all countries that culture koi and/or common carp with the exception of Australia. This 9-page fact sheet is intended to inform veterinarians, biologists, fish producers and hobbyists about KHV disease. Written by Kathleen H. Hartman, Roy P.E. Yanong, Deborah B. Pouder, B. Denise Petty, Ruth Francis-Floyd, Allen C. Riggs, and Thomas B. Waltzek, and published by the UF Department of Fisheries and Aquatic Sciences, April 2013.